Soluble and Cell–Cell-Mediated Drivers of Proteasome Inhibitor Resistance in Multiple Myeloma - Farrell, Mariah L.; Reagan, Michaela R. (Frontiers in Endocrinology, 2018)
It is becoming clear that myeloma cell-induced disruption of the highly organized bone marrow components (both cellular and extracellular) results in destruction of the marrow and support for multiple myeloma (MM) cell proliferation, survival, migration, and drug resistance. Since the first phase I clinical trial on bortezomib was published 15 years ago, proteasome inhibitors (PIs) have become increasingly common for treatment of MM and are currently an essential part of any anti-myeloma combination therapy. PIs, either the first generation (bortezomib), second generation (carfilzomib) or oral agent (ixazomib), all take advantage of the heavy reliance of myeloma cells on the 26S proteasome for their degradation of excessive or misfolded proteins. Inhibiting the proteasome can create a crisis specifically for myeloma cells due to their rapid production of immunoglobulins. PIs have relatively few side effects and can be very effective, especially in combination therapy. If PI resistance can be overcome, these drugs may prove even more useful to a greater range of patients. Both soluble and insoluble (contact mediated) signals drive PI-resistance via activation of various intracellular signaling pathways. This review discusses the currently known mechanisms of non-autonomous (microenvironment dependent) mechanisms of PI resistance in myeloma cells. We also introduce briefly cell-autonomous and stress-mediated mechanisms of PI resistance. Our goal is to help researchers design better ways to study and overcome PI resistance, to ultimately design better combination therapies.